ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI TINGKAT LABA PADA PERUSAHAAN SUBSEKTOR OTOMOTIF DAN KOMPONEN DI BEI TAHUN 2010 SAMPAI 2016 - Abdul Majid (BUANA ILMU, 2018)
ABSTRACT The purpose of this study was to examine the effect of Working Capital to Total Asset (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Asset Turnover (TAT), Net Profit Margin (NPM) and Gross Profit Margin (GPM) to the profit rate. Data obtained by purposive sampling method with criterion (1) Automotive Manufacturing Company and Component which listed in Indonesia Stock Exchange (BEI) and consistent exist during period of research (2010 until 2016), (2) Automotive Company and Component that provide financial statement data during the study period (2010 to 2016). The results of the analysis show that the data used in this study has met the classical assumptions, which include: no multicollinearity symptoms, no autocorrelation, no heteroscedasticity symptoms, and normal distributed data. The research was conducted by using descriptive and verification methods, namely; collecting, presenting, analyzing and testing hypotheses, and making conclusions and suggestions. From the results of the analysis of research data, obtained the following conclusions: partially positively insignificant to profit growth: Working Capital to Total Assets (WCTA), Current Liability to Inventory (CLI), Operating Income to Total Liability (OITL), Total Asset Turnover (TAT), Partially significant positive effect on profit growth: Net Profit Margin (NPM), Partially negatively insignificant to profit growth: Gross Profit Margin (GPM). Simultaneously, the ratio of WCTA, CLI, OITL, TAT, NPM and GPM have a significant influence on Profit level. Contribution given by WCTA, CLI, OITL, TAT, NPM and GPM variable to profit rate equal to 62,9%. Continuity of this research further needs to be done to see the consistency of Ratio results to Profit level for the coming year or other subsector in BEI. Keywords: Working Capital to Total Assets (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Asset Turnover (TAT), Net Profit Margin (NPM), Gross Profit Margin (GPM) and profit growth.